De compagnie des bronzes van binnenuit - De Blick, Luc ([Puurs] : UniBook.com, 2011)
This book presents the history of a unique and one of the major Beldian bronze casting foundry, 'De Compagnie des Bronzes' in Brussels, from the viewpoint of one of its former employees who later became a teacher for metalwork. The history of this foundry is accompanied by more than a thousand images of its productions, brought together from the company archives, newspapers and private photographs
Visuele bedrijfscatalogus